2013
DOI: 10.1111/saje.12022
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment and Trade Openness in Sub‐Saharan Economies: A Panel Data Granger Causality Analysis

Abstract: This study uses annual balanced panel data for 25 sub‐Saharan African economies over the period 1977‐2009 to investigate the Granger causality relationship between trade openness and foreign direct investment (FDI) for the region. We took advantage of recent developments in econometric testing techniques for Granger noncausality heterogeneous panels that takes into consideration the effects of cross section dependence across the units of the panel data set to analyse the trade–FDI nexus in the region. The empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Finally, they suggest developing infrastructure facilities in African countries to attract more foreign investors. Seyoum et al (2014) examined the Granger causality relations between foreign direct investment and trade openness in Sub-Saharan economies using Panel data for 25 sub-Saharan African economies over the period 1977-2009. The results indicated that a bidirectional causality relation was identified between trade openness and foreign direct investment in Sub-Saharan economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, they suggest developing infrastructure facilities in African countries to attract more foreign investors. Seyoum et al (2014) examined the Granger causality relations between foreign direct investment and trade openness in Sub-Saharan economies using Panel data for 25 sub-Saharan African economies over the period 1977-2009. The results indicated that a bidirectional causality relation was identified between trade openness and foreign direct investment in Sub-Saharan economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additional evidence on the interaction between insurance sector activities, banking sector activities and economic growth is provided by carrying out the Emirmahmutoglu and Kose (2011) panel causality test with bootstrapping. This test is the most suitable for our study since it does not require stationarity for all the series in the underlying VAR system and may be applied to panels comprising of stationary, non-stationary, cointegrated and non-cointegrated series (Seyoum et al, 2014). The test is also valid in the presence of cross-sectional dependence.…”
Section: Bootstrap Panel Granger Causalitymentioning
confidence: 99%
“…Trade openness is defined as the ratio of the sum of imports and exports to GDP. Trade openness as an important determinant of the FDI is confirmed by a number of recent studies covering developing and post-communist economies (Tintin, 2013;Seyoum et al, 2014;Thangavelu and Narjoko, 2014). Similarly, other studies (Culem, 1988;Mina, 2007;Antras and Caballero, 2009;Kechagia and Metaxa, 2018) found that higher levels of trade openness attract FDI in a wide variety of developing and developed economies.…”
Section: Ror and Fdi: Analysis And Discussionmentioning
confidence: 70%